Asian Bioethics Conference Brochure - Lasker, Shamima Parvin (Bangladesh Journal of Bioethics, 2018)
20th Asian Bioethics conference has been organized by Bangladesh Bioethics Society in cooperation with SSRC, Planing Division, Ministry of Planning; PMR, DGHS, Ministry of Health & Family Welfare, Bangladesh Medical Research Council (BMRC), Asian Bioethics Association (ABA) and Eubios Ethics Institute on Friday, 22 Nov, 2019 at NEC Auditorium, Planning Ministry, Agargoan, Dhaka. M. A. Mannan MP, Honorable Minister, Ministry of Planning, Government of the People's Republic of Bangladesh has kindly consented to grace the occasion as the Chief Guest. Dr. Md. Murad Hassan MP, Honorable State Minister, Ministry of Information, Government of the People's Republic of Bangladesh; Md. Nurul Amin, Secretary, Planning Division, Ministry of Planning; Prof Dr Abul Kalam Azad, DG, Directorate General of Health Services, Ministry of Health & Family welfare (MOH&FW) will present as Special Guests. Drlegates from 40 couuntries will attend the ABC 20 at Dhaka.